2020
DOI: 10.1080/17437199.2020.1780147
|View full text |Cite
|
Sign up to set email alerts
|

Impact of health warning labels on selection and consumption of food and alcohol products: systematic review with meta-analysis

Abstract: Health warning labels (HWLs) could reduce harmful consumption of food (including non-alcoholic drinks) and alcoholic drinks. A systematic review with meta-analysis using Cochrane methods was conducted to assess the impact on selection (including hypothetical selection) or consumption of food or alcoholic drink products displaying image-andtext (sometimes termed 'pictorial') and text-only HWLs. Fourteen randomised controlled trials were included, three for alcohol, eleven for food. For the primary outcomes, ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(56 citation statements)
references
References 61 publications
3
53
0
Order By: Relevance
“…The (online and lab) studies that focused on studying the graphic images on labels found that they elicited higher negative emotional arousal, fear and reactance, and were not well accepted by the participants. These results are also corroborated by the metanalysis investigating the impact of HWL in both alcohol and food products, and found that while health warning labels reduce product selection compared to no labels, the difference between image-and-text HWLs and text-only HWLs was not statistically significant (although in the former, the effect was slightly larger) [44].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The (online and lab) studies that focused on studying the graphic images on labels found that they elicited higher negative emotional arousal, fear and reactance, and were not well accepted by the participants. These results are also corroborated by the metanalysis investigating the impact of HWL in both alcohol and food products, and found that while health warning labels reduce product selection compared to no labels, the difference between image-and-text HWLs and text-only HWLs was not statistically significant (although in the former, the effect was slightly larger) [44].…”
Section: Discussionsupporting
confidence: 61%
“…There has also been increased research activity, and a number of labelling-related reviews have been published recently. Previous reviews focusing on alcohol HWL operated with a relative scarcity of studies [43], focused only on one aspect of the label (image vs. text) [44] or made a brief narrative overview of health labelling studies as part of broader alcohol labelling [45]. Whilst our work partially overlaps with other reviews in examining the impact of labels, our review adds a thorough and systematic examination of the scope of (quasi-)experimental research on new or enhanced health warning labels, including an overview of the labels used in the studies and the explanatory variables studied.…”
Section: Introductionmentioning
confidence: 99%
“…We will not consider warning labels about the health implications of a product’s energy content to be eligible labels (e.g. Clarke 2020a ; Clarke 2020b ). We will also exclude logos or general health claims providing a summary assessment of the healthiness or content of a product.…”
Section: Methodsmentioning
confidence: 99%
“…Second, previous reviews have also shown differential effects of labelling interventions by study setting (e.g. Clarke 2020a ), and this could have important implications for the implementation of labels in different real-world contexts. Finally, SES could modify any potential impact of energy labelling, and interventions that involve the provision of numeric or text-based information may be less effective in more deprived populations ( Hollands 2016 ; Sarink 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of research has shown that communicating about a products' health harms, for example, through product warning labels and mass media campaigns, is an effective strategy for reducing unhealthy behaviours including cigarette smoking (20,21) , alcohol consumption (22) and sugary drink consumption (22)(23)(24)(25) . Similarly, a recent systematic review found that providing information about the health effects of meat consumption is an effective strategy for reducing intentions to eat meat as well as meat consumption (26) .…”
mentioning
confidence: 99%